PERILAKU AGRESI VERBAL PADA REMAJA - julia aridhona; Barmawi, Barmawi; Dwi Setia, Renika (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Adolescence is a time when an individual is looking for self-identity, they tend to be unstable, like to join in and try something regardless of whether it is right or wrong. Aggressive behavior is behavior that intentionally intends to injure physically, verbally and destroy other people's property. Verbal aggression is swearing, mocking, and belittling. This research uses quantitative descriptive research. This study will obtain actual data about the level of aggressive behavior of students at SMPN2 Vocational Junior High School, Aceh Tamiang Regency. The instrument used in this study is the scale of aggression behavior. The population in this study amounted to 739 students and the sample in this study was 72 students. The findings in this study showed that the categorization of verbal aggression behavior showed that there were as many as 14 subjects (19.4%), the low category which means that students never did verbal aggression behavior towards others, then there were 44 subjects (61.1%). which means that students have done verbal aggression behavior against others, then there are as many as 14 subjects (19.4%) which are included in the high category which means students often do verbal aggression behavior towards others. Keywords: Verbal aggression, behavior, students.